Technician and technical institutions-industry linkages a policy study - Pimentel, Rosario (1981)
This study delves into the forms and constraints and the variables affecting institution-industry linkages in 22 state-supported institutions in Luzon including 14 state universities and colleges of industrial technology, one technician institute, and 7 institutes of industrial technology. The prominent linkages are on the job training of students; industry support for stipends of on the job trainees; in-plant training of technical faculty; joint institution-industry evaluation of on the job training; industry sponsorship of scholarship grants to deserving students; exchange of information and conduct of follow-up studies of graduates. Setting up standards as a joint responsibility of the institution and industry was perceived as one of the gaps in the linkages.
Mimeographed.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Keywords: Industry and education -- Philippines; Technical education -- Philippines